STRATEGI OPTIMALISASI PENERIMAAN PAJAK REKLAME DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN KAMPAR - Suhar, Tini; Wahyu, Hamidi; Sri, Kornita Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to find out the strategy of optimizing the revenue of advertising tax by The Office of Region Income in Kampar Regency. The dependent variable of this research was the improvement of locally generated revenue. The independent variable used was the strategy of optimizing the advertising tax. This research used secondary data obtained from Regional Revenue Agency of Kampar Regency. The research results show that the potency of advertisement tax in 2018 is still low compared to the realization of advertising tax. Total tax calculated in 2018 is IDR 417.730.000. This big potency value must be increased in order to be utilized for local development. The strategy of optimizing tax revenue conducted by the office of Region Income is by optiming the organizational strength and utilizing the opportunity of effective tax revenue.Keywords: taxes, advertising tax, potency